A Practitioner's Guide to Adapting the NIST Cybersecurity Framework - Moskowitz, David (The Stationery Office Ltd, 2022)
The second publication in the Create, Protect, and Deliver Digital Business value series provides practitioners with detailed guidance on creating a NIST Cybersecurity Framework risk management program using NIST Special Publication 800-53, the DVMS Institute's CPD Model, and existing digital business systems.